Scenarios and Road Mapping for KeyTechnologies: Flood and Coastal Defencein Great Britain - Ian Miles (Foresight and STI Governance, 2008)
The Flood and Coastal Defence (FCD) project of the United Kingdom Foresight Programme was involved a scenario exercise that has been very influential on UK policy. The scenario approach had an extensive prehistory, and its use in a water management context predates FCD. It continues to evolve and influence decision-making in many fields. This study presents an overview of the approach and how it has come to be so influential. The FCD project features by an integrated scenario analysis of the factors and consequences of the threat of flooding in the UK for a period of 30 to 100 years. Keywords: technology change; technology development; technology innovation; flood management